Measuring Faculty Viewpoints to Optimize Success for Faculty Researchers: Does Creativity Matter?. Issue 3 (3rd July 2021) - Shreffler, Jacob; Montgomery, Troy; Shreffler, Megan; Bernal, Mateo; Thé, Selena; Danzl, Dan; Mallory, Mary Nan; Huecker, Martin
ABSTRACT: Researchers in higher education seek understanding of techniques to optimize success and produce insightful solutions that make positive impacts on society. We sought to establish howfaculty view creativity in research and distinguish differences in perspectives among faculty stakeholder groups. A survey was employed to higher education faculty and yielded 319 respondents. Results showed creativity is valued less than quality of publications, but more highly than quantity of publications. Additionally, results revealed distinctive differences between the faculty stakeholder groups within our study. This work provides an exploratory lens into the value of creativity for researchers in higher education. By understanding the many facets of faculty advancement, and by recognizing how faculty viewpoints on creativity diverge, researchers can consider how these findings impact their respective work. Furthermore, other researchers can utilize these experimental findings to further explore trends.